Problema Manajemen Pendidikan Dayah Di Aceh - Mukhlisuddin Ilyas (Puslatbang KHAN, 2014)
This paper is a result of a research related to the process and impact of government policies on a Islamic boarding schools education (Pesantren) in Aceh. The study employs a qualitative approach. To collect data, the research uses several techniques such as in-dept interviews, literature study/policy. The result shows that the juridical basis of dayahs education policy in Aceh is based on unlike specialty Act No. 44 of 1999, Act No. 11 of 2006 on Government of Aceh, and Qanun on Organization Structure and Governance of Aceh in 2007. The other regions in Indonesia, which are regulated by dayah education (Pesantren) under the authority of Ministry of Religion Affairs, in Aceh it is controlled by the Government of Aceh Province (Gubernur), by establishing Dayah Education Development Board (BPPD) Provincial and Regency/city. The impact of governments regulation of Province has caused congestion in managing the education management of dayah. Dayah education indicates forfeiture of identity, regulation based on polical practices, policy without design, and recent finding regarding the education model of Islamic boarding schools in Aceh. These subtance are the focus of this paper.